2019
DOI: 10.1111/sms.13434
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term cycling restores endothelial dysfunction after resistance exercise

Abstract: Resistance exercise impairs endothelial function. Therefore, it is of paramount importance to devise an effective strategy for restoring endothelial function after resistance exercise. Herein, we tested the hypothesis that resistance exercise‐induced endothelial dysfunction would be restored by low‐to‐moderate intensity cycling. Seventeen young healthy subjects completed two randomized experimental trials: (a) resistance exercise only trial; and (b) cycling after the resistance exercise trial. Following baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…It has been reported that 8 weeks of aerobic exercise performed after resistance exercise increased resting FMD, while the opposite (aerobic exercise performed before resistance exercise) led to an unchanged FMD (Okamoto et al, 2007). Accordingly, in sedentary subjects, aerobic exercise performed after (Morishima et al, 2019a), but not before (Morishima et al, 2019b), resistance exercise protects against the deleterious effect of resistance exercise on FMD. Whether similar FMD changes occur in endurance and resistance trained subjects is not known and deserves to be studied.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that 8 weeks of aerobic exercise performed after resistance exercise increased resting FMD, while the opposite (aerobic exercise performed before resistance exercise) led to an unchanged FMD (Okamoto et al, 2007). Accordingly, in sedentary subjects, aerobic exercise performed after (Morishima et al, 2019a), but not before (Morishima et al, 2019b), resistance exercise protects against the deleterious effect of resistance exercise on FMD. Whether similar FMD changes occur in endurance and resistance trained subjects is not known and deserves to be studied.…”
Section: Discussionmentioning
confidence: 97%
“…However, no study examined whether a single bout of resistance exercise affects blood Klotho concentration. Conversely, a hypertensive stimulus induced by a single bout of resistance exercise acutely induced endothelial dysfunction (Morishima et al, 2018, Morishima, Iemitsu, et al, 2019Morishima, Toyoda, et al, 2019;Morishima et al, 2020). Given that Klotho is thought to positively affect endothelial function (Keles et al, 2015), we hypothesized that the serum Klotho concentration would decrease All baseline and post measurements were collected in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…In the second visit, subjects were asked to eat a light meal at least 2 h prior to arriving to the laboratory. The method (i.e., a light meal before experiment) has been approved by many researchers in previous studies (Morishima et al 2018; Morishima, Iemitsu, et al, 2019; Morishima, Toyoda, et al, 2019; Restaino et al, 2015, 2016). In addition, subjects were prohibited to take caffeine and alcohol for at least 10 h. They were also not allowed to perform exercise for 24 h prior to the study visit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies also tested the effect of combined aerobic and resistance exercise on endothelial function. In young healthy subjects, impaired endothelial function after the resistance exercise was restored with successive 10-min cycling [112], while 45-min cycling prior to resistance exercise did not prevent the acute impairment in endothelial function after resistance exercise [113]. The detrimental effects of resistance exercise on endothelial function in young healthy subjects was also prevented when resistance exercise was performed at high intensity but with low repetitions [114].…”
Section: Aerobic Versus Resistance Exercisementioning
confidence: 94%